A rancher of his own - Harlen, Brenda (Harlen, Brenda. Match made in Haven., 2025)
"Single dad Andrew Morrow had several reasons for needing a fresh start, but none more important than his two daughters. He's busy transforming the residents' favorite bakery in Haven, Nevada, and his attraction to local rancher Sarah Stafford is a distraction he can't entertain--but the sparks between them are too hot to ignore. Still, he can't afford to lose his heart when he's supposed to be focusing on family...For Sarah, change is long overdue in this sleepy little town--especially the social scene. Then she meets Andrew, and everything inside her goes soft and gooey--like the filling in his delectable beignets. His devotion to his daughters only makes him more appealing, and suddenly Sarah finds herself willing to open her long-guarded heart. But will Andrew let her into his life...for real?" --